High‐Frequency Gravity Waves and Kelvin‐Helmholtz Billows in the Tropical UTLS, as Seen From Radar Observations of Vertical Wind - Ajil Kottayil; Aurélien Podglajen; Bernard Legras; Rachel Atlas; Prajwal K; K. Satheesan; Abhilash S (Geophysical Research Letters, 2024)
Abstract The present study analyzes novel observations of vertical wind (w) in the tropical upper troposphere‐lower stratosphere obtained from a radar wind profiler in Cochin, India. Between December 2022 and April 2023, 63 consecutive 4 hr curtains of w were measured with a vertical spacing of 180 m and a sampling time step of 44 s, thus resolving almost the whole spectrum of vertical motions. Spectra of w strongly vary with altitude. They are generally flat up to the local Brunt‐Väisälä frequency (BVF), but sometimes exhibit a peak of w variance closer to BVF, a feature which may be attributed to trapped gravity waves. At other times and locations, the w profiles reveal Kelvin‐Helmholtz billows. Finally, the variability of w variance over the 4 month campaign period is investigated. Using brightness temperature from geostationary satellites as a convective proxy, it is found that w variance is highly correlated with fluctuations in convective activity.